CORONARY DISEASE AND OSAS: WHAT TO EXPECT AND HOW TO DEAL - Bento, Carmo (2022)
In Portugal, cardiovascular diseases are the main cause of death! One of its risk factors is Obstructive Sleep Apnea Syndrome. This desease increases morbidity, mortality, disability and days of hospitalization. However, in acute myocardial infarction, Sleep Apnea promotes its development and recurrence, but reduce mortality.This investigation aims to evaluate the profile of patients with acute myocardial infarction and previous diagnosis of Obstructive Sleep Apnea Syndrome and to compare them with current scientific knowledge. Thus, data were collected from patients hospitalized for acute myocardial infarction in 2016 (population 1) and patients hospitalized in cardiology, for the same reason, in 2017 (population 2) at Hospital Pêro da Covilhã. Populations 1 and 2 were divided into 2 groups. SAOS group (individuals diagnosed with Obstructive Sleep Apnea Syndrome) and SEM SAOS group (individuals without previous diagnosis of Obstructive Sleep Apnea Syndrome. Excel software was used to make the necessary analyzes. In population 1, the prevalence of Obstructive Sleep Apnea Syndrome was 4% and all individuals in the SAOS group were male. In this group, average age was lower, average days of hospitalization were higher, but their median was exactly the same and mortality and recurrence were lower. In population 2, the prevalence of Obstructive Sleep Apnea Syndrome was 5.9%, also with a predominant male gender. Regarding average age, average days of hospitalization and mortality, the results were similar to those of population 1. However, the median of days of hospitalization in population 2 was higher in the SAOS group. The acute myocardial infarction recurrence was null for both groups.Some data are in agreement with what is expected, like gender of the individuals, average age of infarction, average days of hospitalization and mortality. However, it is important to point out that an underdiagnosis of Obstructive Sleep Apnea Syndrome or a poor / insufficient data collection by the Hospital may have created a bias in the interpretation of the results, since the SAOS groups, of both years studied, were composed of only 3 individuals each. In conclusion, it is advisable to carry out more extensive investigations to clarify the issues pointed above and monitoring of sleep and night oximetry of hospitalized patients for myocardial infarction.